Regime tributário das telecomunicações - Anjos, Rubya Floriani dos (2013)
This paper aims to discuss the telecommunications taxation regime especially with regard to taxes on telecommunications services (which involves communications) and its earnings and infrastructure services. The differential legal liability for this segment and the relevant jurisprudence are also considered as well as the essential aspects of the taxation juridical regimes. In spite of being important, the telecommunications theme is new in the national conjuncture as its effective progress started due to the privatization and monopoly ending in 1997, according to the General Telecommunications Law n. 9.472. Although there has been respectful doctrine about telecommunications taxation, the constant technological development related to it turns the subject present and allows reinterpretations that are proposed by this thesis. The analysis method is based on the understanding of the facts which compound the incidence hypothesis of the taxation rule and especially the communications and telecommunications meanings, among others such as diffusion and information, all of them concerned with those ones. Aiming our proposal, common use concepts, technical Linguistic concepts and taxation, regulatory and constitutional juridical concepts are used to lead into the following results: i) in the private law regulations there isn t a communication concept to which the State Valued Added Tax (ICMS) should consider its incidence; ii) the telecommunications concepts prescribed by the sector rules are not suitable for the State Valued Added Tax incidence (ICMS), but they define the essential comprehensive field of the Contribution for the Social Integration Program (PIS), the Contribution for Social Security Funding (COFINS), the Fund for Universal Access to Telecommunications Services (FUST) and the Contribution for the Fund of Telecommunications Technological Development (FUNTTEL); and iii) the assertion that the telecommunications are species of the communications genus or that the concept of telecommunications defined by the General Telecommunications Law encompasses other services beyond those of the communications is possible depending on the adopted reference. This paper also refers to the Contribution to the Development of National Movies Industry CONDECINE-Telecom as well as to some Administration Regulatory Action Taxes and ends with the presentation of relevant connected subjects such as providing internet access, advertising and publicity circulation together with the most important Superior Court of Justice telecommunications jurisprudence